Penerapan Algoritma C4.5 Untuk Memprediksi Blog Yang Memiliki Peluang Juara - Rita Wati; Kusrini Kusrini; Kusnawi Kusnawi (Fakultas Teknik Universitas Hamzanwadi, 2023)
Blogs are currently not only used as online diaries or online journals. Blog content that supports text, images, videos, gifs, animations, pdfs and YouTube makes the use of blogs more than just online dairy. Currently blog is one of the media used by companies and organizations in promoting goods and services. The existence of bloggers is needed by companies and organizations to review their products and services with the aim of attracting online customers. One of the efforts to invite bloggers to be able to review products in an interesting way has led business actors to become interested in holding blog contests. In this research, a model was built to predict blogs that have a chance to win by applying the C4.5 decision tree algorithm. The prediction model was created using 100 blog contest participant data obtained from three blog competitions organized by ASUS which were obtained through the contest participant links found on the committee blog. From the processed dataset, supporting seven variables including Word Count, DA, PA, Image Template, Domain and Champion. The resulting prediction model is a decision tree with 7 attributes which produces 11 leaves and 18 trees with an accuracy of 74% with a precision of 0.735 and a recall of 0.740.